Historical Memory in the Context of the Historical Education - Селищева, Ірина Анатоліївна (Pedagogy of Higher and Secondary Education, 2017)
The article deals with the phenomenon of historical memory, and studies the connection between historical memory and historical education. The attention is focused on the factors that led to revaluation effects, events in national history today. The notion of historical memory has emphasized that the structure of historical memory includes individual and collective memory. It has been found that the basis of national identity makes historical memory. It is emphasized that the role of history education should be the formation of the younger generation in a holistic way past the historic national community with which young people can identify themselves. There should be a Ukrainian perspective on events both in the world and in Ukraine, taking into consideration world experience that tolerances towards human rights, human values and civilization values culture. However, a detailed study of historical events, identifying positive interference of different cultures, critical analysis and open discussion of sensitive and controversial issues contributes to overcoming social prejudices and stereotypes. That history education should help with this. It is pointed that the modern history education has the potential to become a factor of reconciliation of different models of historical memory, a means of constructive public dialogue of past and current problems of social development. It is reported that since 1991 in Ukraine emerged the need to overcome the one-sidedness and bias distorted presentation of national history, in an effort to highlight the historical process objectively, taking into account all factors of influence, according to the achievements of world historical science. Despite the fact that during the period of independence laid the foundations of a new system of teaching the history of Ukraine and World History, revised or even completely updated the content of history education, still many outstanding issues both theoretical and practical level.